Analysis of Regional Financial Management Performance Ratios on Economic Growth in the Era of Fiscal Decentralisation in Karanganyar Regency Central Java - Wijayanti, Ratna Ayu; Huda, Syamsul (PT Inovasi Pratama Internasional, 2025)
Economic growth is a crucial aspect of development, especially in developing countries, as it has a direct impact on people's welfare. Welfare improvement cannot be separated from the role of the government in managing regional finances optimally. Regional financial management that applies the concept of value for money can encourage economic growth, so as to improve people's welfare. This study aims to analyse the effect of regional financial performance on economic growth. The object of this research is Karanganyar Regency using data for the period 2013-2023. The analysis method used is multiple linear regression with the help of SPSS IBM 26 software. The results showed that the regional independence ratio had a positive but insignificant effect on economic growth. Meanwhile, the effectiveness ratio has a negative and significant effect on economic growth. The efficiency ratio is proven to have a positive and significant effect on economic growth. The ratio of the degree of fiscal decentralisation has a negative but insignificant effect on economic growth.